Effects of replacing diet beverages with water on weight loss, carbohydrate and lipid metabolism during a hypoenergetic diet - Madjd Jabari, Seyedeh Ameneh (2017)
This thesis compared the effect on weight loss of either replacing diet beverages (DBs) with water or continuing to consume DBs (study 1 in healthy overweight and obese, n=89 and study 2 in patients with type 2 diabetes, n=81) adults during a 24-wk weight-loss program (for study1 and 2) and 18 month weight loss and weight maintenance plan (for study3, n=89). In study 1, compared with the DB group, the water group had a greater decrease in weight (1.2kg more weight loss in the water group compared with the DBs Group ,P=0.015), BMI (0.5 kg/m² more BMI reduction in the water compared with the DBs Group ,P=0.002), fasting insulin (1 mU/l more Fasting insulin reduction in the water compared with the DBs Group,P<0.001), homeostasis model assessment of insulin resistance (HOMA-IR)(0.2 more HOMA-IR reduction in the water compared with the DBs Group, P<0.001) and 2-h postprandial glucose(0.305 mmol/l more 2hpp reduction in the water compared with the DBs Group,P<0.001). In study 2, weight (2.5 kg more weight loss in the water compared with the DBs Group, P=0.005) and BMI (0.9 kg/m² more BMI reduction in the water group compared with the DBs Group, P=0.005) decrease after 18 months in the water group compared with the DBs group was significant. There was also a greater reduction in fasting insulin levels (1.8 mU/l more Fasting insulin reduction in the water group compared with the DBs Group,P<0.001), better improvement in HOMA-IR (0.5 more HOMA-IR reduction in the water group compared with the DBs Group, P<0.001), a greater decrease in 2-h postprandial plasma glucose (0.5 mmol/l more 2hpp reduction in the water group compared with the DBs Group, P<0.001) and glycated hemoglobin (0.2 more HbA1c reduction in the water group compared with the DBs Group, P=0.030) in the water group compared with the DBs over 18 months. In study 3, obese participants with Type 2 diabetes in the water group of study 2 had more weight loss (1.16 kg more weight loss in the water group compared with the DBs Group, P=0.006) and BMI (0.5 kg/m² more BMI reduction in the water group compared with the DBs Group, P=0.006). Also reduction of fasting insulin (1.6 mU/l more Fasting insulin reduction in water group compared with DBs Group,P<0.001), fasting plasma glucose (0.3mmol/l more Fasting plasma glucose reduction in the water group compared with the DBs Group, P=0.003), HOMA-IR (0.7 more HOMA-IR reduction in the water group compared with the DBs Group, P=0.003) and 2 hour postprandial glucose (0.3 mmol/l more 2hpp reduction in the water group compared with the DBs Group, P=0.027) was greater in the water group. By contrast, changes in waist circumference and lipid profiles were not significantly different between the two groups in these three studies. Replacement of DBs with water after the main meal in obese and overweight healthy and type 2 diabetic women who were regular users of DBs may cause greater weight reduction during 24 weeks and also in the longer period of an 18 month weight management program. In addition, replacement of DBs with water offers clinical benefits to improve insulin resistance. Generally, better improvements in energy and carbohydrate metabolism may occur when water rather than DBs is consumed over a weight loss program.